P Profil Senyawa Alkaloid Dengan Metode Spektroskopi Inframerah (FTIR) Dan Penetapan Kadar Total Alkaloid Dari Ekstrak Daun Jarak Pagar (Jatropha curcas .L) - Gamah, Gamah; Nastiti, Kunti; Aryzki, Saftia (LPPM Universitas Sari Mulia, 2023)
Background: Jatropha curcas leaves (Jarropha Curcas L.) is a plant that has potential medicinal properties. Empirically, Jatropha leaves (Jarropha Curcas L.) are used by the people of South Kalimantan to expedite the delivery process. One of the compounds that have pharmacological properties in Jatropha curcas leaves is alkaloids. Objective: Knowing the alkaloid compounds using infrared spectroscopy (FTIR) and determining the total alkaloid content of jatropha leaf extract (Jatropha Curcas L) leaf extract. Methods: This study used descriptive qualitative analysis to identify alkaloid functional groups from FTIR results and quantitative analysis to determine total alkaloid content. Results: Preliminary test results using thin layer chromatography on Jatropha curcas leaves (Jatropha Curcas.L) were positive for containing alkaloid compounds. The FTIR results showed that there was an alkaloid compound content in the presence of functional groups which were obtained C-H, C=O, C-O, N-H and aromatic C-H which are characteristics of alkaloid compounds and the total alkaloid content was obtained 5,645 % (g/5g). Conclusion: Jatropha curcas leaf extract (Jatropha curcas L) using FTIR analysis showed the content of alkaloid compounds and the total alkaloid content obtained was 5,645 % (g/5g).